(untitled) (Journal of Geography and Environmental Management, 2017)
Irreversible collection of Amudarya and Syrdarya water for irrigation has led to a decrease, and then to almost complete cessation of the flow of these rivers into the Aral Sea. Violation of the natural balance of runoff and evaporation, under which the Aral existed, led to the Aral ecological catastrophe – the death of delta and sea ecosystems and irreversible changes in the natural environment of the Turan lowland. As the sea level decreases, a new land appears each year, and the one that is located in the rear part of the dehydration undergoes an extraordinary transformation in extra-arid climatic conditions. The main natural factor influencing the development and formation of natural complexes on the dried bed of the Aral Sea is underground groundwater. This affects the structure of the emerging natural complexes or landscapes that form a number of dynamic regional bands and isolated areas on the dried day. In the article is given an assessment of the results of groundwater monitoring monitoring of the dried part of the Aral Sea. Characteristics of the level and hydrochemical regimes of groundwater are given for three hydrogeological sections: Sudochye-Adzhibay, Muinak and Akkalinsky.